TRADITIONAL PHRASEOLOGISMS IN UZBEK LANGUAGE - Abdujalilova, Feruza (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract: These article to phraseologisms in the Uzbek language, in which the components of clothing are antonyms to each other, we cited as an example the phrase "There is a belt at the waist", "Human walk without an appetite". Because these phraseologisms give a bold and low-key content: when an Uzbek person wants to know if he is reliable, appointed, Dionysius, "Does he have a belt on his back?", he says.